Pengaruh Influencer, Brand Trust Dan Media Sosial Terhadap Repurchase Intention Bakso Mas Roy Cabang MERR Surabaya - Muhammad Rizal Maulana; Ida Bagus Cempena (Nirta Learning Centre, 2025)
This study aims to analyze and examine the influence of Influencers, Brand Trust, and Social Media on Repurchase Intention at Bakso Mas Roy, MERR Surabaya branch. A quantitative method was used in this research, involving a sample of 100 respondents collected through questionnaires. The data analysis techniques applied included Descriptive Analysis, Instrument Testing, Classical Assumption Testing, and Hypothesis Testing using SPSS. The study was conducted from February to March 2025.The findings show that all indicators used in the research are valid and reliable. Based on the results of the Multiple Linear Regression analysis, the Social Media variable had the most dominant influence, while the Brand Trust variable showed the lowest influence. The T-test results indicate that Influencers have a significant partial effect on Repurchase Intention, Brand Trust also has a significant partial effect on Repurchase Intention, and Social Media has a significant partial effect on Repurchase Intention. The F-test results show that simultaneously, Influencers, Brand Trust, and Social Media significantly influence Repurchase Intention at Bakso Mas Roy, MERR Surabaya branch. Furthermore, the Coefficient of Determination (R²) test indicates that the independent variables explain 95.4% of the variation in Repurchase Intention, while the remaining 4.1% is influenced by other factors outside the model.